2000
DOI: 10.1016/s0165-0270(00)00173-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing spatial vision — automated measurement of the contrast-sensitivity function in the hooded rat

Abstract: The contrast-sensitivity function (CSF) provides a concise and thorough description of an organism's spatial vision; it is widely used to describe vision in animals and humans, to track developmental changes in vision, and to compare vision among different species. Despite the predominance of rats in neuroscience research, their vision is not thoroughly studied due to the complexity of psychophysical measurement and a generally held notion that rat vision is poor. We therefore designed an economical and rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 31 publications
6
58
0
3
Order By: Relevance
“…To put this visual performance into perspective, both the absolute maximal contrast sensitivity and the spatial frequency at which it is observed are not dissimilar to those of the domestic cat [9]. Indeed, the peak sensitivity is around 10 times that seen in the rat, and at a similar spatial frequency [11]. This is particularly impressive considering the much poorer light gathering power of these apposition compound eyes compared with their vertebrate counterparts [1], and the famously high temporal resolving power of fly photoreceptors-around five times faster than in mammals [20].…”
Section: (B) Contrast Sensitivity For Large Patterns In Vertebratesmentioning
confidence: 92%
See 1 more Smart Citation
“…To put this visual performance into perspective, both the absolute maximal contrast sensitivity and the spatial frequency at which it is observed are not dissimilar to those of the domestic cat [9]. Indeed, the peak sensitivity is around 10 times that seen in the rat, and at a similar spatial frequency [11]. This is particularly impressive considering the much poorer light gathering power of these apposition compound eyes compared with their vertebrate counterparts [1], and the famously high temporal resolving power of fly photoreceptors-around five times faster than in mammals [20].…”
Section: (B) Contrast Sensitivity For Large Patterns In Vertebratesmentioning
confidence: 92%
“…the threshold contrast is around 0.5% [6,8]. Psychophysical analysis of other vertebrate species reveals slightly less impressive contrast sensitivity: peaks are around 116 in cats [9]; less than 30 in typical rodents [10,11]; in the 7-30 range in various bird species (for review, see [12]); and around 50 in goldfish [13].…”
Section: (B) Contrast Sensitivity For Large Patterns In Vertebratesmentioning
confidence: 99%
“…Our lab [18] and others [7,13,22,23] have reported that the adult grating acuity of normal Long-Evans strain rats is around 1.0 cycle/degree (c/d). We have also reported that visual deprivation in rats during a physiologically-defined critical period early in life [26] results in significantly reduced visual acuity [19].…”
Section: Introductionmentioning
confidence: 93%
“…Starting at a frequency 20% of the acuity, the contrast was decreased linearly from 100 to 22% at the acuity limit. These values are derived from the figures of Keller et al [13], but are somewhat more conservative. The low frequency rolloffs, and the overall lower contrast sensitivity of the rat versus the human that they report were not incorporated.…”
Section: Image Filteringmentioning
confidence: 99%
“…The CS literature contain examples of CS functions that have been obtained from humans De Valois et al, 1974;Elliott, 1987;Sloane, Owsley, & Jackson, 1988), macaques (De Valois et al, 1974), squirrel monkeys (Merigan, 1976), owl monkeys (Jacobs, 1977), bush babies (Langston, Casagrande, and Fox, 1986;Bonds et al, 1987), cats Maffei, 1974: Blake et al, 1974;Aiken and Loop, 1990), dogs (Aiken and Loop, 1990), rats (Birch and Jacobs, 1979;Silveira, L. C. L., Heywood, C. A., and Cowey, A., 1987;Legg, 1984;Keller et al, 2000), ground squirrels (Jacobs et al, 1980), tree squirrels (Jacobs, Birch, and Blakeslee, 1982), tree shrews (Petry, Fox, and Casagrande, 1984), opossums (Silveira, Picanco-Diniz, and Oswaldo-Cruz, 1982), rabbits (Pak, 1984;Kulikowski, 1978), goldfish (Bilotta and Powers, 1991;Northmore and Dvorak, 1979), sunfish (Celenza, 1994), quail (Lee, Holden, and Djamgoz, 1997), pigeons (Hodos et al, 2002;Nye, 1968), an eagle (Reymond and Wolfe, 1981), and a kestrel (Hirsch, 1982). These functions encompass both electrophysiological and behavioral data.…”
Section: Overviewmentioning
confidence: 99%